WHISTLEBLOWER (SAKSI PELAPOR) DAN PERANANNYA DALAM MEMERANGI FRAUD (DILIHAT DARI PERSPEKTIF ETIKA & HUKUM) - Yulianto Dirdjosumarto (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2015)
War against fraud is not easy, however fraud must be minimized or reduced. Based on the report of the Association of Certified Fraud Examiners (ACFE), the most effective method to detect fraud is information obtained from the whistleblowers through the tip mechanism. It means that every organization or company should design and develop whistleblowing system. In Indonesia, whistleblowers have significant roles to encourage the law enforcement. The requirements of whistleblowing regarded as ethical behaviour are as follows : (1). fraud is significant; (2). based on the real & valid data; (3). whistleblower’s motivation is to decrease the harm of others; (4). the internal solution has been conducted. The legal protection for whistleblowers in Indonesia is based formally on the law no. 13/2006 and SEMA no.4 / 2011. To avoid external whistleblowing, the organizations or companies should involve some steps as follows : implementing an effective system of internal control; designing and developing whistleblowing system; and conducting good corporate governance and encouraging open and honest culture.